2013
DOI: 10.1051/meca/2013086
|View full text |Cite
|
Sign up to set email alerts
|

Least action criteria for blind separation of structural modes

Abstract: -It was recently shown that blind source separation (BSS), as originally developed in the signal processing community, can be used in operational modal analysis to separate the responses of a structure into its individual modal contributions. This, in turn, allows the application of simple single-of-degreefreedom techniques to identify the modal parameters of interest. Several publications have recently attempted to give a posteriori physical interpretations to BSS -as initially developed in telecommunication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…However, in this case, the eigenvalues of the right part of equation ( 11) are the squares of the natural frequencies. The minimization of the cost function minimizes the variance of the spectra of the sources, which is similar to the minimum spectrum variance criterion (Antoni et al, 2014). The smooth orthogonal decomposition (Zhou and Chelidze, 2008) (SOD)-based modal analysis approach is also similar to this approach.…”
Section: Choosing the Weighting Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this case, the eigenvalues of the right part of equation ( 11) are the squares of the natural frequencies. The minimization of the cost function minimizes the variance of the spectra of the sources, which is similar to the minimum spectrum variance criterion (Antoni et al, 2014). The smooth orthogonal decomposition (Zhou and Chelidze, 2008) (SOD)-based modal analysis approach is also similar to this approach.…”
Section: Choosing the Weighting Matrixmentioning
confidence: 99%
“…To verify the theoretical findings, FSOBI is used to identify modal parameters from the experimental data (Antoni et al, 2014), and the results are compared with those from the SOBI method. The structure is a scale model of a wind turbine blade shown in Figure 11(a).…”
Section: Experimental Workmentioning
confidence: 99%
“…Abazarsa et al [9] adopted a second-order blind identification (SOBI) technique to nonclassically damped systems. Antoni et al [10] showed that several separation criteria purposely dedicated to operational modal analysis (OMA) can be deduced from general physical considerations. Sadhu et al [11][12][13] took use of multirank parallel factor decomposition, time-series analysis-based BSS, and a decentralized BSS algorithm for ambient modal identification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, independent component analysis (ICA) combined with wavelet transform has been used to identify damage for time-varying systems [24]. Therefore, the study of output-only modal analysis based on ICA is of great significance [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation